Performance improvement through internal control, experience and individual rank - Wardayati, Siti Maria; Miqdad, Muhammad; Efendi, Husnul Irfan; Arisandy, Frisma Novela (Journal of Contemporary Accounting, 2019)
This research was conducted to see and assess the extent to wich employee performance can consistently maintain the quality of health centers that it provides. Moreover, it also aims to examine and analyze the effects of internal control, experience and individual rank factors on the employee performance using multiple regression analysis to test the hypothesis. This study uses simple random sampling method to obtain 37 respondents working at the Health Centers of Jember as the research samples. The data used are primary data obtained from the respondents directly through questioners. The results show that control activities and individual rank have significant effect on the employees performance, whereas control environment, risk assessment, information and communication, supervision, and experience do not significantly affect the employees performance at Health Centers of Jember. The implications of this research show that an increase in control activities and employees competence will improve the performance of the Health Center.